THE INFLUENCE OF ELECTRONIC MEDICAL RECORD IMPLEMENTATION AND HEALTHCARE WORKERS’ DIGITAL LITERACY ON PATIENT SERVICE EFFICIENCY IN HOSPITALS - Dian Prawibawa; Kosasih (RADJA PUBLIKA, 2026)
This study examines the effect of Electronic Medical Record (EMR) Implementation (X1) and Digital Literacy (X2) on Patient Service Efficiency (Y) at Hospital X. The research employed a quantitative approach with a descriptive design. Data were collected from 41 healthcare staff using a structured questionnaire and analyzed using multiple linear regression. Classical assumption tests, including normality, multicollinearity, and heteroscedasticity, were conducted to ensure the validity and reliability of the regression model. The results indicate that EMR Implementation has a significant positive effect on Patient Service Efficiency, demonstrating that the effective use, integration, and accessibility of EMR systems are crucial for enhancing hospital service efficiency. In contrast, Digital Literacy shows a positive but not statistically significant effect, suggesting that while digital skills are necessary, they have a limited impact without robust system implementation and organizational support. Simultaneously, EMR Implementation and Digital Literacy together significantly influence Patient Service Efficiency, with the regression model explaining 61.5% of the variance.